2009
DOI: 10.4236/jbise.2009.23025
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of bone condition by acoustic emission technique: A review

Abstract: The paper deals with the review of acoustic emission technique in biomedical field. The re-view is done with the aim to provide an overview of the use of AE technique in biomedical field, mainly concentrated on the AE behavior of bone under different loading conditions, its depend-ence on strain rate, in osteoporosis, monitoring the fracture healing process of bone. The over-all conclusion from the review was that almost all the studies in bone indicated that the initial AE occurs only in the plastic region an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 51 publications
0
15
0
Order By: Relevance
“…Cortical bone has also been examined by AE to monitor microdamage during fatigue, although large data scatter prohibited further data analysis [21]. Numerous biomedical applications of AE analysis demonstrate its potential as a non-invasive method to determine bone state under in vivo conditions [22]. This includes characterization of bone healing [23] and monitoring of implants [24].…”
Section: Introductionmentioning
confidence: 99%
“…Cortical bone has also been examined by AE to monitor microdamage during fatigue, although large data scatter prohibited further data analysis [21]. Numerous biomedical applications of AE analysis demonstrate its potential as a non-invasive method to determine bone state under in vivo conditions [22]. This includes characterization of bone healing [23] and monitoring of implants [24].…”
Section: Introductionmentioning
confidence: 99%
“…In recent years there has been increasing interest in translational applications of acoustic science to inform the diagnosis and management of several different health [31][32][33][34][35][36][37][38][39] and dental conditions [40,41]. In this context, the development of techniques to measure highfrequency AE in knee joints [16][17][18][19] offers the potential to develop a biomarker reflecting the integrity of interactions between knee joint components during weightbearing movement.…”
Section: Acoustic Emissionmentioning
confidence: 99%
“…Shrivastava, and Prakash reviewed the use of acoustic emissions for assessing bone condition [8]. Frank et al concluded that the analysis of knee joint sounds could be used for distinguishing normal from abnormal cartilage surfaces, and for classifying disorders of the joint [9].…”
Section: Introductionmentioning
confidence: 99%